2002
DOI: 10.1016/s0014-5793(02)03781-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a new dual‐functional caffeine synthase gene encoding an enzyme for the conversion of 7‐methylxanthine to caffeine from coffee (Coffea arabica L.)1

Abstract: In co¡ee and tea plants, ca¡eine is synthesized from xanthosine via a pathway that includes three methylation steps. We report the isolation of a bifunctional co¡ee ca¡eine synthase (CCS1) clone from co¡ee endosperm by reverse transcriptionpolymerase chain reaction (RT-PCR) and rapid ampli¢cation of cDNA ends (RACE) technique using previously reported sequence information for theobromine synthases (CTSs). The predicted amino acid sequences of CCS1 are more than 80% identical to CTSs and are about 40% similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(131 citation statements)
references
References 26 publications
(34 reference statements)
7
116
0
8
Order By: Relevance
“…On the other hand, expression analyses of N-methyltransferase cDNA sequences mainly performed by RT-PCR, as well as by classical Northern-blot experiments, showed that the 7-methylxanthosine synthase encoding gene (designated CaXMT1 by Uefuji et al, 2003 or CmXRS1 by Mizuno et al, 2003b) was expressed to equal levels both in developing endosperm and in young leaves. Genes coding for the theobromine synthase (designated CaMXMT1 of CaMXMT2 by Uefuji et al, 2003 or CTS1 andCTS2 by Mizuno et al, 2003a) and caffeine synthase (designated CaDXMT1 by Uefuji et al, 2003 or CCS1 by Mizuno et al, 2003a) were also expressed in immature coffee fruits (as in stage 6-7 corresponding to endosperm expansion; Keller et al, 1972). In addition, the CTS2 gene expression appeared high not only in whole small green fruits (diameter 10mm) but also in the pericarp and immature endosperm of larger fruits (diameter 15mm) (Mizuno et al, 2003a).…”
Section: Gene Expression During Coffee Fruit Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, expression analyses of N-methyltransferase cDNA sequences mainly performed by RT-PCR, as well as by classical Northern-blot experiments, showed that the 7-methylxanthosine synthase encoding gene (designated CaXMT1 by Uefuji et al, 2003 or CmXRS1 by Mizuno et al, 2003b) was expressed to equal levels both in developing endosperm and in young leaves. Genes coding for the theobromine synthase (designated CaMXMT1 of CaMXMT2 by Uefuji et al, 2003 or CTS1 andCTS2 by Mizuno et al, 2003a) and caffeine synthase (designated CaDXMT1 by Uefuji et al, 2003 or CCS1 by Mizuno et al, 2003a) were also expressed in immature coffee fruits (as in stage 6-7 corresponding to endosperm expansion; Keller et al, 1972). In addition, the CTS2 gene expression appeared high not only in whole small green fruits (diameter 10mm) but also in the pericarp and immature endosperm of larger fruits (diameter 15mm) (Mizuno et al, 2003a).…”
Section: Gene Expression During Coffee Fruit Developmentmentioning
confidence: 99%
“…Genes coding for the theobromine synthase (designated CaMXMT1 of CaMXMT2 by Uefuji et al, 2003 or CTS1 andCTS2 by Mizuno et al, 2003a) and caffeine synthase (designated CaDXMT1 by Uefuji et al, 2003 or CCS1 by Mizuno et al, 2003a) were also expressed in immature coffee fruits (as in stage 6-7 corresponding to endosperm expansion; Keller et al, 1972). In addition, the CTS2 gene expression appeared high not only in whole small green fruits (diameter 10mm) but also in the pericarp and immature endosperm of larger fruits (diameter 15mm) (Mizuno et al, 2003a). Interestingly, RT-PCR experiments did not reveal expression of CaXMT1, CaMXMT1, CaMXMT2 and CaDXMT1 genes in mature (stage 10; Keller et al, 1972) fruits , which could explain the absence of caffeine accumulation during the final ripening process (stages 9 to 11; Keller et al, 1972).…”
Section: Gene Expression During Coffee Fruit Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…e Taking into account the presence of conserved protein domains and the expression patterns and/or experimentally determined functions reported for the putative homologs of these sequences in Arabidopsis or other plant species. young floral buds, flowers and fruits, specially in the endosperm tissue (Mizuno et al, 2003).…”
Section: Characterization Of Genes Upregulated During Citrus Flower Dmentioning
confidence: 99%
“…N-methyltransferase proteins have also been purified (Mazzafera et al, 1994;Mösli Waldhauser et al, 1997;Moisyadi et al, 1998). Subsequently, cDNAs for 7-methylxanthine methyltransferase (MXMT or theobromine synthase) were successfully cloned from coffee plants (Ogawa et al, 2001;Mizuno et al, 2003).…”
Section: Physiological and Biochemical Advancesmentioning
confidence: 99%